Proper Construction And Set Up Of Malaysian Fish Aggregating Devices (Unjam) - Ibrahim, Sakri (1991)

(untitled)
This study was carried out with an objective of improving the durability of unjams and determining the rational arrangement and optimum density of unjams . Several experiments were conducted in coastal waters of Terengganu in the South China Sea to determine a safe anchoring power of unjams and parameters required for the development of mathematical models that could produce an optimum trapping efficiency .Experiment s on anchoring power showed sandy bottom giving the highest value of fixing coefficient ( 0. 953 ) , foll owed by muddy bottom ( 0. 903 ) , and sandy -mud bottom ( 0.731 ) . This value was found to be higher for two sandbags tied one behind the other than for two sandbags tied in one lump.The unjam's anchor was found to have a reserved fixing force of 67 . 34 kg , which is 93 . 86% in excess of what was required to anchor a n unjam in place .